Keanekaragaman Tanaman Pangan yang Dipedagangkan di Pasar Grogol dan Pasar Telukan, Kabupaten Sukoharjo, Indonesia - Daiva Ardhania Nirwasita Hartono; Jamilatun Nisa; Intan Ardhana Riswari; Umi Mahmudah; Widhi Himawan; Ahmad Dwi Setyawan (Politeknik Negeri FakFak, 2024)
Traditional markets are central to community economic activities and play a significant role in the distribution of local food products. Therefore, markets reflect the diversity of food crop commodities available in a region. This diversity holds vital importance in supporting human health balance. The more diverse the plant species available in a region, the greater the variety of nutrients that can be obtained, such as minerals, vitamins, fiber, and other essential nutrients. Furthermore, the diversity of food crops is also valuable from cultural and environmental conservation perspectives. This study aims to identify and document the diversity of food crops traded in Grogol Market and Telukan Market, Sukoharjo Regency, Central Java. The research employs a qualitative descriptive method. Data were collected through observations and semi-structured interviews using an ethnobotanical with 55 respondents who are traders in both markets. The data were then classified based on family, edible plant parts, and commodity categories. The study's findings revealed that 124 species or varieties of plants from 39 families are traded in Grogol Market and Telukan Market. The Zingiberaceae family has the highest number of species found in both markets. Vegetables are the largest commodity group traded, followed by fruits, spices, and staple foods. The parts of plants traded include fruits, leaves, tubers, seeds, rhizomes, stems, and flowers. Based on the results, the diversity of food crops traded in Grogol Market and Telukan Market is relatively high, reflecting local potential that supports community health, cultural heritage, and environmental sustainability.